ICT Learning Media Design Using Smart Apps Creator at SMA N 1 Kapur IX - Nurazila; Musril, Hari Antoni; Okra, Riri; Derta, Sarwo (BiCED Proceeding, 2023)
This research was motivated by problems found after direct interviews with ICT subject teachers at SMA N 1 Kapur IX Mr. Diki Putra Indri S.Kom on November 26, 2022 and 11 students. Based on these interviews, the authors identified problems, namely the disruption of the learning process due to power outages, many students already have an android but its utilization in the field of education is still limited, there is no android-based learning media at SMA N 1 Kapur IX. Based on the problem, the author designs ICT learning media so that it can be utilized validly, practically and effectively. The method used is Research and Development (R&D) with the PPE development model which consists of: Planning, Production, Evaluation. The resulting media was tested for validity, practicality and effectiveness using a product assessment questionnaire. The research results are presented in the form of ICT learning media accessed by android. The validity test of four experts resulted in a value of 0.89 which indicates validity. The practicality test involving three experts resulted in a score of 0.97 with a very high category. The effectiveness test, with one teacher and 31 students, produced a coefficient of 0.88 with a high effectiveness category.